2010
DOI: 10.1097/aln.0b013e3181cded07
|View full text |Cite
|
Sign up to set email alerts
|

Residual Paralysis after Emergence from Anesthesia

Abstract: Support was provided solely from institutional and/or departmental sources. Benoît Plaud and Bertrand Debaene have participated in the clinical development of sugammadex as coinvestigators in two phase III studies funded by Schering-Plough Corporation, Oss, The Netherlands. François Donati and Jean Marty have no conflicts of interest. The figures and tables in this article were prepared by Dimitri Karetnikov, 7 Tennyson Drive,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
122
1
21

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 198 publications
(144 citation statements)
references
References 44 publications
0
122
1
21
Order By: Relevance
“…This is also the level of neuromuscular blockade at which reversal with acetylcholinesterase inhibitors is possible. 1 After sugammadex 2 mgÁkg -1 iv, the median time to obtain a TOF ratio (TOFR) C 0.9 was reported as 1.4(0.9-5.4) min and 2.1(1.6-64.2) min for rocuronium 2 and vecuronium, 3 respectively. After neostigmine 50 lgÁkg -1 iv, this delay was reported as 18.5(3.7-106.9) min and 21.9(2.9-76.2) min for rocuronium 2 and vecuronium, 3 respectively.…”
Section: Résumémentioning
confidence: 99%
“…This is also the level of neuromuscular blockade at which reversal with acetylcholinesterase inhibitors is possible. 1 After sugammadex 2 mgÁkg -1 iv, the median time to obtain a TOF ratio (TOFR) C 0.9 was reported as 1.4(0.9-5.4) min and 2.1(1.6-64.2) min for rocuronium 2 and vecuronium, 3 respectively. After neostigmine 50 lgÁkg -1 iv, this delay was reported as 18.5(3.7-106.9) min and 21.9(2.9-76.2) min for rocuronium 2 and vecuronium, 3 respectively.…”
Section: Résumémentioning
confidence: 99%
“…Anticholinesterase agents enhance spontaneous recovery; as a result, they are more effective against intermediate-acting than long-acting agents because the former have a more rapid spontaneous recovery. This explains why residual paralysis is more frequent with long-acting agents 3,19 and why there has been a decrease in the reported incidence of TOFR \ 0.9 since the late 1970s as long-acting agents were replaced progressively with intermediate-acting agents (Fig. 1).…”
Section: Role Of Neuromuscular Blocking Agentmentioning
confidence: 99%
“…To reach a TOFR of 0.9 within 10-15 min, it is now recommended to wait until four twitches are seen, with or without fade. 3 When deep blockade is present (zero to three twitches present), there are no advantages in giving neostigmine early, even in large doses ([ 50 lgÁkg -1 ). When neostigmine is given early, studies have shown that the time from neostigmine administration to full recovery is no shorter than the time until four twitches reappear spontaneously plus the time from administering neostigmine at four twitches to full recovery (Fig.…”
Section: Ceiling Effectmentioning
confidence: 99%
See 2 more Smart Citations